Problem odpowiedzialności za nienależyte wykonanie obowiązku informacyjnego: [Liability for the improper fulfillment of information duty] (Studia Prawnicze / The Legal Studies, 2017)
Zgodnie z podstawowym założeniem przyświecającym europejskiemu prawu konsumenckiemu, odpowiedzialność wobec konsumenta powinna speł-niać kryterium zarówno efektywności, jak i proporcjonalności, co oznacza, iż nie należy mieć wyłącznie na uwadze odpowiedzialności pojmowanej czysto formal-nie, tj. jako utrzymanie ekonomicznej równowagi stron. Sankcja, jaką ponieść ma profesjonalista, służyć ma realnemu zaspokojeniu interesu konsumenta, a nie sprawić tylko, iż jego bilans rachunkowy będzie pozytywny. Dodatkowo sankcje za niedopełnienie obowiązków informacyjnych powinny skłaniać przedsiębior-ców do przestrzegania tych przepisów. In European contract law and consumer law the nature of protection through information is based on imposing on business an obligation to make a declaration of knowledge to a consumer, which should enable them to make a rational decision. The implementation of efficient regulations regarding the liability for the improper fulfillment of information duties aims to maintain the level of trust between contracting parties on optimal level, and, as a result, to lead to balancing of their position respecting the freedom of contract principle. Polish model of consumer protection through information, in particular in the area of the liability for the improper fulfillment of information duties by business requires a lot of changes. In national law it is specially problematic, the lack of definition of general, legal consequences of failure to provide obligatory information, providing it in an incomplete, unclear way, but without the intention to mislead the other party.